32-40 Summer Street, ca, 1980 - Unknown (Tufts Archival Research Center, 2005)
Elevated view north-northeast (left to right) of 32-40 Summer Street, located between Washington Street to the north-northwest and Arch Street to the south-southeast. Signage adorns the facades of the buildings, which face west-southwest. Street lights, traffic signals, traffic lights and pedestrians line the sidewalk along the east-northeast side of Summer Street. Automobiles are included in the photograph. 7 1/4 x 7 7/16 overall Photographs